العشوائيــات من منــظور القانـون العــام - هاشم محمد أحمد الجحيشي; إيمان ثابت يونس الطائي (PROSPECTIVE RESEARCHES, 2023)
Those who scrutinize consideration of the phenomenon of indiscriminate construction (shanty houses) and encroachment on stateowned lands find that it carries with it many problems that reflect negatively on social interest, foremost among which is visual pollution, distortion of urban planning, and a lack of services, not to mention that it constitutes an environment fertile to the proliferation of factors that drive criminal behaviors in relation to some of them, such as begging, immoral crimes and the nucleus of criminal gang formation due to the need and denial of the most basic human rights, at a time when the state has a duty to combat that uncivilized phenomenon by the means of law intention on the one hand, and working to contain it by eliminating its causes by raising the economic level by improving individual income, providing job opportunities، and resolving the housing crisis, especially in central and southern Iraq on the other hand, and dealing realistically with the problem by resorting to the application of the theory of balancing benefits and harms in the event that it is presented The administration’s decision to remove before the court in compliance with the dictates of the rules of national and international human rights.